Empresses and queens in the courtly public sphere from the 17th to the 20th century - Romberg, Marion; Romberg, Marion (Brill's studies on art, art history, and intellectual history, 2021)
"The book analyzes the evolving interaction between court and media from various perspectives. Eight case studies focus on different European Empress consorts and Queen regnants from the 17th to the 20th centuries, using a unique, comparative, cross-media, and cross-period approach. The volume raises a multitude of issues, ranging from how female figures were achieved public prominence through their portraits; how their faces and bodies were moulded and rearticulated to fit varying expectations in multiple public spheres; and the degree to which they, as female subjects, engaged with or had agency within the processes of production and reception. In particular, two types of female rulership are contrasted, their relationship to diverse media explored, and lesser-known and under-researched dynastic women are spotlighted. Contributors include: Christine Engelke, Anna Fabiankowitsch, Inga Lena Ångström Grandien, Titia Hensel, Andrea Mayr, Alison McQueen, Marion Romberg, and Alison Rowley"--